USING NETWORK-BASED EDUCATIONAL AND METHODOLOGICAL COMPLEXES IN PROFESSIONAL TRAINING OF FUTURE LECTURERS - Kryvorot, Tetiana; Pryhodi, Mykola (Professional Pedagogics, 2020)
Relevance: at the current stage of society, networks are being introduced to many industries and the education system is no exception. Preparing for the use of networking technologies is an important step in the education of students at a higher education institution. Aim: illumination of the problem of realization of educational process on the basis of network educational-methodical complexes and development of methodology of application of network technologies in preparation of future teachers. Methods: analysis, systematization and generalization; observation, questioning and questioning; experiment, methods of mathematical statistics (criterion χ2). Results: the problems of the educational environment based on modern information and communication technologies with the use of Internet technologies are considered. It is proved that the use of network educational and methodical complexes is effective for activating educational and cognitive activity of students. The concept, structure and content of the network educational and methodical complex are specified, the prospects of its use are substantiated, as well as the focus on activation, individualization and innovation of the educational process. Methodological issues of improving the quality of educational services using remote technologies are considered. Features of creation of network educational and methodical complexes are established, theoretical bases of selection and structuring of educational materials and their short characteristic are presented. The network educational and methodical complex "Fundamentals of Scientific Research" on the basis of the open platform Moodle, which consists of organizational-informational, operational-activity, motivational-communication and evaluation blocks, has been developed and implemented. Conclusions: The characteristics of criteria, indicators, levels of assessment of training of future teachers are revealed and the results of experimental research on approbation of network educational and methodical complex are resulted. It is proved that the differences between the control and experimental groups are statistically significant, which confirms the effectiveness of the proposed method.